The Electro-Oxidation of Lactic Acid at Platinum Microparticles and Polycrystalline Platinum Electrode - Sedenho, Graziela C. [UNESP]; Lee, Patricia T.; Toh, Her Shuang; Salter, Chris; Johnston, Colin; Stradiotto, Nelson R. [UNESP]; Compton, Richard G. (Esg, 2016)
We report the electrochemical modification of boron-doped diamond electrode surface with electrodeposited platinum microparticles of mean size of 193 nm +/- 107 nm. The activity of platinum microparticle modified boron-doped diamond (ca. 20 % platinum coverage) and platinum macro electrodes (100% platinum coverage) are measured and compared through lactic acid oxidation, selected because of the surface sensitive nature of the reaction. Significant differences are found with the modified BDD showing a markedly lower current density.
Keywords: platinum microparticles; lactic acid oxidation; boron-doped diamond; modified electrodes; polycrystalline platinum